The Effect of Spirulina (Spirulina platensis) Supplementation on Production and Feed Efficiency of Laying Hens - Tistiana, Heli; Setyawan , Enrico Brilly Fermi Yudo (Faculty of Animal Science, Universitas Brawijaya, 2025)
This study aims to determine the effect of adding spirulina on feed consumption, hen day production, egg weight, egg mass, and feed conversion in laying hens. The quail used was strain Hy-line at 89-95 weeks of age with a population 150 chicks. the basal feed used is quail feed for the layer phase produced by PT. Charoen Pokphand Indonesia. Feeding treatment used addictive (Spirulina platensis) purchased from e-commers. The method used was a completely randomize design consisting of 5 treatments and 5 replications. The addition of spirulina with a T? level (0%), T? level (0.25%), T? (0.5%), T? (0.75%), and last T? (1%). If it has a significant effect, it will be tested using Duncan’s multiple range test method. The result showed that the addition of spirulina to quail feed had no significant effect on feed consumption, hen day production, egg weight, egg mass, and feed conversion (P>0.05). The conclusion from the study, the addition of spirulina to feed gave the best result at an addition of (0.75%) for feed conversion.